On criticism - Carroll, Noël (Routledge, 2009)
In a recent poll of practicing art critics, 75 percent reported that rendering judgments on artworks was the least significant aspect of their job. This is a troubling statistic for philosopher and critic Noel Carroll, who argues that that the proper task of the critic is not simply to describe, or to uncover hidden meanings or agendas, but instead to determine what is of value in art.